An overview on the conventional and nonconventional methods for manufacturing the metallic glasses - Axinte, E. (EDP Sciences, 2017)
Metallic glasses (MGs), first discovered in 1959 at Caltech are currently among the most studied metallic materials. MGs called also glassy metals, amorphous metals, liquid metals, are considered to be among the materials of the future. The classic methods for industrialization of MGs are: end-casting in copper molds and protected environment, die forging, atomization for obtaining MG powder,selective laser melting, imprinting in molds, thermoplastic shaping in the super-cooled temperature region. These methods are suitable for producing high value-added precision components but the problems still exists: expensive tools, limited lifetime of tools and the occurring of crystallization. Actually methods (thermoplastic shaping, casting and die forging) are limited by the low flexibility of production and by higher costs of tools and accessories. More suitable methods are greatly desired to machine MGs for their wider applications. © 2017 The Authors, published by EDP Sciences.